Persepsi Kondisi Kerja dan Kinerja Karyawan Generasi Y - Tri Yulyanti Fathonah; Aida Vitayala Hubeis; Nurmala Katrina Panjaitan (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2016)
Generation Y is the latest generation of workers entering the workforce nowadays. The increasing number of generation Y entering the workforce nowadays has provided challenges for PT XYZ. The purposes of this research are to analyze the perception of generation Y employees toward the working conditions at PT XYZ and to analyze the performance of generation Y employees at PT XYZ. The research was conducted at PT XYZ involving generation Y employees as respondents. Data was collected using questionnaires, interviews, and documentation. Respondents were selected by simple random sampling. The research sample were 66 employees, consisted of 46 men and 20 women  employees. The initial stage of data analysis was conducted using descriptive statistics, linear regression analysis and Mann Whitney test using SPSS version 16. The research found that employees generation Y both men and women have positive perception of working conditions at XYZ. The average value scores of generation Y employees' performance based on gender leads to positive. The performance indicator that has the highest value on the employees of Generation Y (both men and women and has positive perception is cooperative attitude. Strategies that suggested to maintain and improve employee performance they are review of policy determination of salary and benefits are calculated based on performance standards and real-time based on the results of the employee according to his duties and responsibilities, giving reward as appreciation to employees who have achieved maximum performance results, as well as scheduling fun activities gathering and team building in order to improve teamwork between colleagues and give refreshment to the employees in the middle of their routine work.